Significantly reduced adsorption and activation of blood components in a membrane oxygenator system coated with crosslinkable zwitterionic copolymer. (August 2016) - Wang, Yan-Bing; Shi, Ke-Hui; Jiang, Hong-Li; Gong, Yong-Kuan
Graphical abstract: Abstract: A crosslinkable zwitterionic copolymer PMBT was coated onto the surfaces of polypropylene hollow fiber membrane (PP-HFM) oxygenator and its connecting tubes. The PMBT copolymer coating on the oxygenator circuit formed a cell outer membrane mimetic surface with excellent stability. The hemocompatibility of the PMBT copolymer coated PP-HFM oxygenator circuit was evaluated by animal extracorporeal circulation. The concentrations of clotting components fibrinogen and platelet in the blood were almost unchanged during the circulation through the PMBT copolymer coated oxygenator circuits. By contrast, the concentrations of fibrinogen and platelet were significantly reduced to 52% and 56% respectively in the uncoated oxygenator group due to adsorption and thrombogenesis of the blood during 2 h circulation. Moreover, concentration of activation marker beta-thromboglobulin for platelet in the blood was remarkably lower in the PMBT group than the uncoated control group ( p  < 0.01). All the results strongly supported that the hemocompatibility of the PP-HFM oxygenator circuit could be improved significantly by coating a stable and densely assembled zwitterionic polymer film. This simple, stable and highly effective cell membrane mimetic coating strategy may be applicable in developing advanced oxygenator systems and other artificial organs. Statement of Significance: Although a number of studies have reported the fabrication of zwitterionic phosphorylcholine coated oxygenators to resist the adsorption and activation of blood components and eliminate heparin-induced thrombocytopenia, none of them have fabricated stable and densely assembled film, especially with crosslinkable amphiphilic random copolymer described in our manuscript. The novel features of our work include: The first study of fabricating crosslinked and densely assembled zwitterionic copolymer coating on surfaces of a commercial oxygenator system. The first study on hemocompatibility of both the PMBT coated and the bare commercial PP-HFM oxygenator circuits by animal extracorporeal circulation. Much better hemocompatibility was measured on the PMBT coated oxygenator circuit compared with the bare and other polymer coated oxygenator systems.